How students' obstacle in solving mathematical tasks deal with linear equation in one variabel - Wicaksono, Agung; Prabawanto, Sufyani; Suryadi, Didi (Universitas Islam Raden Intan Lampung, INDONESIA, 2024)
Background: Algebra is one of the most important topics in school mathematics. However, the facts in the field found that there were still many errors made by students in solving problems on linear equations in one variable.Aim: This research aims to describe and analyze students' learning obstacles in one-variable linear equation material.Method: This research used a qualitative research approach with a phenomenological design. This research used a purposive sampling technique, the research subjects were 28 class VIII students of Junior High School in Palu City. Data collection was carried out by triangulating data through description tests, in-depth interviews, and documentation studies.Result: Learning obstacles found in the one-variable linear equation material are categorized into 3 types, namely ontogenic obstacles, epistemological obstacles, and didactical obstacles. ontogenic obstacles are found because there is a leap in students' thinking from an arithmetic mindset to an algebraic mindset. Epistemological obstacles are found due to limited context for students which causes errors in working on questions. Some epistemological obstacles are the concept of linear equations, algebraic operations, and applications to equations. The didactical obstacle was found because the teacher's teaching was procedural so the formation of the concept of one-variable linear equations and inequalities in students did not go well.Conclusion: The importance of initial strengthening is related to students' understanding of coefficients, variables, and constants, providing strengthening of the arithmetic thinking process to algebraic thinking, as well as techniques and methods in delivering material and the teaching materials used.